2020
DOI: 10.1021/acs.jcim.9b00806
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Reaction Dynamic Coupling in Histidine Kinases: Insights from Hybrid QM/MM Simulations

Abstract: Histidine kinases (HK) of bacterial two-component systems represent a hallmark of allosterism in proteins, being able to detect a signal through the sensor domain and transmit this information through the protein matrix to the kinase domain which, once active, autophosphorylates a specific histidine residue. Inactive-to-active transition results in a large conformational change that moves the kinase on top of the histidine. In the present work, we use several molecular simulation techniques (Molecular Dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…To build our model, we have relied on distinct in silico approaches. Methodological choices are closely based on the rationale adopted in a similar study by one of the authors on enzymatic stereoselectivity and are in line with options suggested in several reviews referenced earlier. , In the Supporting Information, we evaluate the reliability of our choices, focusing on the following aspects: (1) the suitability of both chosen MD approaches to evaluate % reac and Δ F ⧧ and their statistical validity, (2) the suitability of the semiempirical QM method DFTB3/O-Phyd in evaluating Δ F ⧧ , especially in relation to other methodological options ,, ,,,,,,,, and whether benchmarking is satisfactory, and (3) how well sampling along the relatively simple RC Enz and RC Sub still manages to capture chemical changes involving other QM atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To build our model, we have relied on distinct in silico approaches. Methodological choices are closely based on the rationale adopted in a similar study by one of the authors on enzymatic stereoselectivity and are in line with options suggested in several reviews referenced earlier. , In the Supporting Information, we evaluate the reliability of our choices, focusing on the following aspects: (1) the suitability of both chosen MD approaches to evaluate % reac and Δ F ⧧ and their statistical validity, (2) the suitability of the semiempirical QM method DFTB3/O-Phyd in evaluating Δ F ⧧ , especially in relation to other methodological options ,, ,,,,,,,, and whether benchmarking is satisfactory, and (3) how well sampling along the relatively simple RC Enz and RC Sub still manages to capture chemical changes involving other QM atoms.…”
Section: Resultsmentioning
confidence: 99%
“…In silico case studies (e.g. refs and to mention only a few recent studies) point to a plethora of accessible reaction pathways, for which it is exceedingly difficult to predetermine a suitably descriptive reaction coordinate (cf. Results and Discussion).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study both the phosphotransfer and the phosphatase reaction mechanisms, we used a multiple steered molecular dynamics (MSMD) strategy, combined with Jarzynski's relationship to determine the corresponding Free Energy Profiles. This strategy has already been shown to be useful in previous works from our group for phosphoryl transfer reactions 35,53,54 . Briefly, in MSMD the system is driven "multiple" times along the selected reaction coordinate under nonequilibrium conditions, by applying an external force, and for each individual trajectory, the work performed by the external force is computed.…”
Section: Multiple Steered Molecular Dynamics Protocolmentioning
confidence: 89%
“…The copyright holder for this preprint this version posted November 12, 2021. ; https://doi.org/10.1101/2021.11.12.468217 doi: bioRxiv preprint strategy has already been shown to be useful in previous works from our group for phosphoryl transfer reactions 35,53,54 . Briefly, in MSMD the system is driven "multiple" times along the selected reaction coordinate under nonequilibrium conditions, by applying an external force, and for each individual trajectory, the work performed by the external force is computed.…”
Section: Multiple Steered Molecular Dynamics Protocolmentioning
confidence: 99%